PERUBAHAN STRUKTUR MODAL MENYEBABKAN PERUBAHAN KINERJA KEUANGAN - Otniel Safkaur; Lesi Hertati (Jurnal Ilmu Keuangan dan Perbankan, 2020)
This research is conducted at Foreign Banks in Indonesia Data analysis techniques used is SEM. The results showed that changes in capital structure caused changes in financial performance. Problems between company managers and lenders and problems between company managers and company owners. The problem between company managers and creditors lies in the company's inability to return borrowed funds due to the misconduct or decisions of company managers. The role of the capital structure of financial institutions is similar to other non-financial companies where some of the opinions were based on the theory of Perfect World.